Policy programs and service delivery models for older adults and their caregivers: Comparing three provinces and two states. (18th May 2022) - Peckham, Allie; Saragosa, Marianne; King, Madeline; Roerig, Monika; Shaw, James; Bornstein, Stephen; McGrail, Kimberlyn; Morris, Madeline; Young, Yuchi; Papenkov, Maksim V.; Marchildon, Greg
Abstract: Despite an increase in prevalence of complex chronic conditions and dementia, long‐term care services are being continuously pushed out of institutional settings and into the home and community. The majority of people living with dementia in Canada and the United States (U.S.) live at home with support provided by family, friends or other unpaid caregivers. Ten dementia care policy programs and service delivery models across five different North American jurisdictions in Canada and the U.S. are compared deductively using a comparative policy framework originally developed by Richard Rose. One aim of this research was to understand how different jurisdictions have worked to reduce the fragmentation of dementia care. Another aim is to assess, relying on the theory of smart policy layering, the extent to which these policy efforts 'patch' health system structures or add to system redundancies. We find that these programs were introduced in a manner that did not fully consider how to patch current programs and services and thus risk creating further system redundancies. The implementation of these policy programs may have led to policy layers, and potentially to tension among different policies and unintended consequences. One approach to reducing these negative impacts is to implement evaluative efforts that assess 'goodness of fit'. The degree to which these programs have embedded these efforts into an existing policy infrastructure successfully is low, with the possible exception of one program in NY.